Uma Evolução Tranquila: o surgimento de parcerias intergovernamentais indígenas-locais no Canadá: Povos indígenas e Governos Locais no Canadá - Soares, Leonardo Barros (Departamento de Estudos Latino-Americanos - ELA, 2020)
In the book reviewed, Alcantara and Nelles seek to understand what types of cooperative relationship exist between indigenous peoples and local governments in Canada and which factors explain their emergence. Initially, they propose a theoretical framework capable of providing a model of analysis for the problem raised. Following this, for fieldwork and case studies, the researchers selected four small-town neighboring communities - the Batchewana First Nation and Garden River First Nation and the city of Sault Ste Marie; the Teslin Tinglit Council and the city of Teslin; Champagne and Aishihik First Nations and the city of Haines Junction; Viger First Nation Malecite and Les Basques Regional Municipality - in three provinces - Yukon Territory, Québec and Ontario. In these locations, they interviewed thirty civil servants, as well as indigenous leaders and activists, to build a typology of intergovernmental relations between indigenous peoples and local governments and to present a set of theoretical and empirically informed factors. En el presente trabajo, Alcantara y Nelles buscan comprender qué tipos de relaciones de cooperación existen entre los pueblos indígenas y los gobiernos locales en Canadá y qué factores explican su surgimiento. Inicialmente, proponen un marco teórico capaz de proporcionar un modelo de análisis para el problema planteado. Después de esto, para el trabajo de campo y los estudios de caso, los investigadores eligieron cuatro comunidades vecinas de pequeños pueblos: la Primera Nación Batchewana y la Primera Nación Garden River y la ciudad de Sault Ste Marie; el Consejo Teslin Tinglit y la ciudad de Teslin; Champagne y Aishihik Primeras Naciones y la ciudad de Haines Junction; Viger First Nation Malecite y Les Basques Regional Municipality - en tres provincias - Territorio de Yukon, Québec y Ontario. En estos lugares, entrevistaron a treinta funcionarios públicos, así como a líderes y activistas indígenas, a fin de construir una tipología de las relaciones intergubernamentales entre los ...